THE UTILITY OF DIGITAL ILLUSTRATIVE VISUALS IN THE DEVELOPMENT OF GRAPHIC DESIGN WITHIN THE REGIONAL CONTEXT OF MAHARASHTRA - Mandre, Shailesh Bajirao; Dr Atre Avadhut, Dr Atre Avadhut (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The primary goal of the study is to understand the utility of digital illustrative visuals in the development of graphic design in Maharashtra. The research has been meticulously structured, incorporating sections on introduction, aim, methodology, importance, history, discussion, case studies, advantages, disadvantages, implications for the future, and concluding remarks. The study employs a qualitative method to systematically assess the data through interviews, observations, and case studies. The literature within this document provides relevant data, along with links, charts, and visuals pertaining to the subject of study. The main outcomes are constructive. The digital illustrations have brought revolutionary positive changes in the graphic design sectors of Maharashtra. It has been established that the effective use of human hand skills and intelligence is used to create quality digital illustrative visuals through computers. The findings and interpretation aligned closely with the research title. The arrival of computers in Maharashtra post-1984 led to a swift uptake of the more efficient 'Desk-Top Publishing (DTP)' model by 1995. Presently, the most advanced generation of computers is operating in Maharashtra. This period marked the evolution of 'digital illustrative visuals' as artists experimented with a combination of manual and digital methods (collaborative methods). The digital method has become highly convenient for illustrators, producing creative results similar to traditional visual art. The utilization of 'Digital Illustrative Visuals' offers numerous advantages, including the swift creation of creative imaginative visuals, the ability to easily edit any image, and the resolution of issues related to human errors, time consumption, and quality.